The Future of Work in Sub-Saharan Africa - Abdychev, Aidar (Departmental Papers; Departmental Paper ;, 2018)
Far-reaching changes in technology, climate, and global economic integration are transforming the world of work in ways that we do not yet fully understand. Will the swift technological advances of the Fourth Industrial Revolution raise the standards of living for everyone? Or will robots massively displace workers leading to a jobless future where only a few benefit from the fruits of innovation? Will mitigation efforts be able to cushion the adverse effects of climate change, including food shortages and mass migration, which would place extra pressure on urban labor markets? Will countries continue to integrate commercially and financially, fostering growth and employment? Or will trade wars become a norm in a world increasingly fragmented and inward-looking? In sub-Saharan Africa, these uncertainties meet a dramatic increase in population and a rapid expansion in the labor force, which is becoming increasingly urban.